Antibiofilm efficacy of green synthesized graphene oxide-silver nanocomposite using Lagerstroemia speciosa floral extract: A comparative study on inhibition of gram-positive and gram-negative biofilms. (February 2017) - Kulshrestha, Shatavari; Qayyum, Shariq; Khan, Asad U.
Abstract: Biofilm architecture provides bacteria with enhanced antibiotic resistance, thus raising the need to search for alternative therapies that can inhibit the bacterial colonization. In the present study, we synthesized graphene oxide-silver nanocomposite (GO-Ag) by non-toxic and eco-friendly route using a floral extract of Legistromia speciosa (L.) Pers. The gas chromatography-mass spectrometry (GC-MS) analysis of plant extract revealed the presence of compounds which can simultaneously act as reducing and capping agents. The sub-inhibitory concentrations of synthesized GO-Ag reduced the biofilm formation in both gram-negative ( E. cloacae ) and gram-positive ( S. mutans ) bacterial models. Growth curve assay, membrane integrity assay, scanning electron microscopy (SEM) and confocal scanning laser microscopy (CSLM) revealed different mechanisms of biofilm inhibition in E. cloacae and S. mutans. Moreover, quantitative RT-PCR (qRT-PCR) results suggested GO-Ag is acting on S. mutans biofilm formation cascade. Biofilm inhibitory concentrations GO-Ag were also found to be non-toxic against HEK-293 (human embryonic kidney cell line). The whole study highlights the therapeutic potential of GO-Ag to restrain the onset of biofilm formation in bacteria. Highlights: Green synthesis of GO-Agusing floral extract of Lagerstroemia speciosa (L.) Pers. Phytochemical analysis of floral extract using GC-MS. Determination of antibiofilm properties of synthesized GO-Ag. Results revealed different mechanisms of biofilm inhibition in E. cloacae and S. mutans . An in-depth analysis of mode of action of GO-Ag in bacterial biofilm inhibition.